2008
DOI: 10.1016/j.jpainsymman.2007.10.023
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Open, Parallel Group, Multicenter Trial to Investigate Analgesic Efficacy and Safety of a New Transdermal Fentanyl Patch Compared to Standard Opioid Treatment in Cancer Pain

Abstract: A new 72-hour transdermal fentanyl matrix patch has been designed, which has a 35%-50% reduction of the absolute fentanyl content compared with other currently available transdermal fentanyl patches that are using the matrix technology. The new patch has previously been shown to be pharmacokinetically bioequivalent to the marketed fentanyl patch. To determine noninferiority in efficacy in cancer patients and to compare safety, a clinical trial comparing the new fentanyl patch with standard oral or transdermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…The newer style patch appears to be pharmacokinetically bioequivalent to the marketed fentanyl patch. 22 Another new administration method is iontophoresis through a battery-operated, patient-controlled transdermal system (PTCS); this process drives medication deep into the dermis with a weak electrical current. 23 The pharmacokinetic properties of the PCTS are similar to those of intravenous fentanyl infusion and appear to be unaffected by gender, age, race, or weight.…”
Section: Transdermal Deliverymentioning
confidence: 99%
“…The newer style patch appears to be pharmacokinetically bioequivalent to the marketed fentanyl patch. 22 Another new administration method is iontophoresis through a battery-operated, patient-controlled transdermal system (PTCS); this process drives medication deep into the dermis with a weak electrical current. 23 The pharmacokinetic properties of the PCTS are similar to those of intravenous fentanyl infusion and appear to be unaffected by gender, age, race, or weight.…”
Section: Transdermal Deliverymentioning
confidence: 99%
“…For the reason that most patients in this study suffered from chronic visceral pain and/or bone pain but not neuropathic origin [2,31] Many studies demonstrated that one of the advantages of TDF was significantly lower incidence of AEs especially constipation compared to other oral opioids used for pain control, while some others reported the equal incidence , analgesic effect was remarkable. [32] Respiratory depression is the most serious and potentially life-threatening adverse effect. In the postmarketing experience, deaths from hypoventilation due to inappropriate use of TDF have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…36 Studies indicate that fentanyl patches are effective when compared to the standard forms of opioid management for both acute and chronic pain (e.g., in palliative care and with cancer pain). 18,37 Several studies have found a reduction in certain side effects (including constipation, opioid-associated pruritus, and sedation) in those receiving fentanyl patches compared to other standard pain therapies (e.g., use of extended-release oral morphine). 18,38 Fentanyl is relatively contraindicated in opioid-naïve patients, those with known or suspected paralytic ileus, or those with a history of significant respiratory disease (e.g., severe bronchial asthma, severe chronic obstructive pulmonary disease, cor pulmonale, hypercapnia).…”
Section: Fentanyl (Duragesic/mylan)mentioning
confidence: 99%